PENGARUH ARUS LALU LINTAS TERHADAP PANJANG ANTREAN MENGGUNAKAN REGRESI LINEAR - Ridayati - (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Poor traffic arrangements will cause congestion and accidents that could endanger human life, evenmore to the increasing of Traffic in Yogyakarta. The aims of this paper are: first, to identify the level of service provided by the three signalized intersections “Jogja Phone” Yogyakarta at the present time. Furthermore, the result of level of service analysis is low in F level. By re reffing the cycle time the level service is increasing to B. Second, the result used SPSS had known that there was a significantly influence between green ratio, degree of saturation, traffict flow, road capacitysimul-taneously with long queue.